Genetics and pathophysiology of haemophagocytic lymphohistiocytosis. (12th July 2021) - Meeths, Marie; Bryceson, Yenan T.
Abstract: Haemophagocytic lymphohistiocytosis (HLH) represents a life‐threatening hyperinflammatory syndrome. Familial studies have established autosomal and X‐linked recessive causes of HLH, highlighting a pivotal role for lymphocyte cytotoxicity in the control of certain virus infections and immunoregulation. Recently, a more complex etiological framework has emerged, linking HLH predisposition to variants in genes required for metabolism or immunity to intracellular pathogens. We review genetic predisposition to HLH and discuss how molecular insights have provided fundamental knowledge of the immune system as well as detailed pathophysiological understanding of hyperinflammatory diseases, highlighting new treatment strategies.